2002
DOI: 10.4315/0362-028x-65.8.1240
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Arcobacter butzleri, a New Waterborne Pathogen, to Water Distribution Pipe Surfaces

Abstract: The capability of Arcobacter butzleri to attach to various water distribution pipe surfaces, such as stainless steel, copper, and plastic, was evaluated using scanning electron microscopy. Our results indicated that Arcobacter cells could easily attach to all surface types and the number of attached cells depended on the length of exposure and temperatures (4 and 20 degrees C). Extracellular fibrils were also observed on the stainless steel surface, especially after 72 h of contact times at both refrigeration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 29 publications
3
56
0
1
Order By: Relevance
“…These considerations together with the ability of A. butzleri to adhere to different surfaces (23) and to form biofilm (16,24) suggest two main sources of contamination in the investigated cheese factory: contaminated raw milk and resident strains able to survive in the wet dairy environment, characterized by large amounts of water and abundant organic material known to enhance the survival of A. butzleri (10).…”
Section: Discussionmentioning
confidence: 99%
“…These considerations together with the ability of A. butzleri to adhere to different surfaces (23) and to form biofilm (16,24) suggest two main sources of contamination in the investigated cheese factory: contaminated raw milk and resident strains able to survive in the wet dairy environment, characterized by large amounts of water and abundant organic material known to enhance the survival of A. butzleri (10).…”
Section: Discussionmentioning
confidence: 99%
“…Besides environmental sources, researchers have observed Arcobacter spp. such as Arcobacter butzleri, A. cryaerophilus, and A. skirrowii in patients with diarrhea and/or food-borne illness (13,30,33,49,60), which has led to these microbes being characterized as potential food-and waterborne pathogens (1,26). Moreover, the presence of Arcobacter in livestock and processed meat (28,29,48) suggests that animals may also serve as possible reservoirs for Arcobacter species.…”
mentioning
confidence: 99%
“…Arcobacter have been identified in water distribution pipe biofilms (Assanta et al, 2002) and on slaughter equipment in poultry abattoirs (Houf et al, 2002;Ferreira et al, 2013). This, coupled with the observation that Arcobacter can survive long periods in water (Van Driessche and Houf, 2008), or even replicate at slaughter and refrigeration temperatures 4 to 10 °C (Kjeldgaard et al, 2009) could place it in a very different level of risk compared to the other campylobacters.…”
Section: Watermentioning
confidence: 99%
“…Arcobacter has been shown to possess the ability to form biofilms (Fernandez et al, 2008;Kjeldgaard et al, 2009;Ferreira et al, 2013) and has been identified in biofilms in drinking water distribution pipes (Assanta et al, 2002), which has the potential to contribute to gastrointestinal illness in people who consume such water.…”
Section: Drinking Watersmentioning
confidence: 99%